Metformin inhibits pathological retinal neovascularization but promotes retinal fibrosis in experimental neovascular age-related macular degeneration - Wang, Xin; Liang, Xu; Huang, Shiya; Wei, Mingyan; Xu, Yuan; Chen, Xiaodong; Miao, Yanliang; Zong, Rongrong; Lin, Xiang; Li, Shiying; Liu, Zuguo; Chen, Qian (Frontiers in Pharmacology, 2025)
PurposeThis study aims to investigate the effects and mechanism of action of metformin on retinal neovascularization and fibrosis in a mouse model of neovascular age-related macular degeneration (nAMD).MethodsVery low-density lipoprotein receptor knockout (Vldlr−/−) mice, a mouse model of nAMD, were used in this study. Vldlr−/− mice were administered metformin on postnatal day (P) 20 for 20 days (early stage of pathological change) or at 5.5 months of age for 45 days (late stage of pathological change). Retinal leakage was examined by fundus fluorescein angiography (FFA). Retinal neovascularization was assessed by lectin staining. Retinal fibrosis was assessed by Western blotting, immunofluorescence staining, and Masson’s trichrome staining.ResultsRetinal vascular leakage and neovascularization were significantly reduced in Vldlr−/− mice treated with metformin compared to those treated with the vehicle at P40. The protein levels of inflammatory factors and phospho(p)-STAT3 were decreased, and P38 and ERK signaling were suppressed in the retinas of metformin-treated Vldlr−/− mice relative to those in the control group at P40. Fibrotic markers were upregulated in the retinas of Vldlr−/− mice treated with metformin compared to those treated with the vehicle at 7 months. Levels of the inflammatory factors and p-STAT3 were increased, and PI3K/AKT, P38, and ERK signaling were upregulated in the retinas of metformin-treated Vldlr−/− mice compared to those in the control group at 7 months.ConclusionMetformin inhibits pathological retinal neovascularization but promotes fibrosis in experimental nAMD. These results provide evidence and highlight important considerations for the clinical use of metformin in different stages of nAMD.